2004
DOI: 10.1103/physrevc.69.034010
|View full text |Cite
|
Sign up to set email alerts
|

Three-body problem with short-range forces: Renormalized equations and regulator-independent results

Abstract: We discuss effective field theory treatments of the problem of three particles interacting via short-range forces. One case of such a system is neutron-deuteron ͑nd͒ scattering at low energies. We demonstrate that in attractive channels the renormalization-group evolution of the 1 + 2 scattering amplitude may be complicated by the presence of eigenvalues greater than unity in the kernel. We also show that these eigenvalues can be removed from the kernel by one subtraction, resulting in an equation which is ren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 48 publications
5
69
0
Order By: Relevance
“…In this work we have extended the subtraction formalism developed previously [13,32] to higher orders in the R/a 2 expansion. Using analytical and numerical arguments we have shown that the three-body system at NNLO can be renormalized without the need for a second three-body datum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we have extended the subtraction formalism developed previously [13,32] to higher orders in the R/a 2 expansion. Using analytical and numerical arguments we have shown that the three-body system at NNLO can be renormalized without the need for a second three-body datum.…”
Section: Discussionmentioning
confidence: 99%
“…With Eq. (18) in hand resolvent identities may be used to obtain the subtracted amplitude at any energy [13]: (19) where the second inhomogeneous term is given by…”
Section: Three-body Scattering At Leading Ordermentioning
confidence: 99%
“…κ * 1/|a|. The hyperradial formalism is particularly well-suited to the analysis of that limit, as the hyperradial potential is a power law (or, more generally, sum of powers of r s /R) for all values of R. In this section we use a momentum-space formalism [20] to obtain the corrections to the Efimov spectrum for arbitrary values of 1/(aκ * ). Numerical calculation of scattering and bound-state observables is straightforward, and it is easy to compute range correctionsregardless of the value of a [10].…”
Section: The Linear Range Correction For Arbitrary Scattering Lementioning
confidence: 99%
“…Ref. [18] showed that this removes this sensitivity of the low-energy amplitude to the choice of Λ. Afnan and Phillips subsequently demonstrated that this result can also be obtained by making a subtraction on the original integral equation, in order to render its kernel better behaved [21].…”
Section: Epj Web Of Conferencesmentioning
confidence: 97%